2013
DOI: 10.1159/000351797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auto-Servo Ventilation on Patients with Sleep-Disordered Breathing, Stable Systolic Heart Failure and Concomitant Diastolic Dysfunction: Subanalysis of a Randomized Controlled Trial

Abstract: Background: Systolic heart failure (HF) is frequently accompanied by diastolic dysfunction and sleep-disordered breathing (SDB). Objectives: The objective of this subset analysis was to determine effect sizes of auto-servo ventilation (ASV and biphasic positive airway pressure ASV) on echocardiographic measures of diastolic function in patients with systolic HF and SDB. Methods: Thirty-two patients with stable systolic HF, concomitant diastolic dysfunction [age 66 ± 9 years old, left ventricular (LV) ejection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Adaptive servoventilation (ASV) has so far been applied to patients with CPAP-resistant and emergent CSA as well as in heart failure patients with Cheyne-Stokes respiration (CSA-CSR) [13][14][15][16][17][18][19]. A number of studies has shown a normalized breathing pattern and even improved exercise capacity in patients with CSA-CSR [16,19,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive servoventilation (ASV) has so far been applied to patients with CPAP-resistant and emergent CSA as well as in heart failure patients with Cheyne-Stokes respiration (CSA-CSR) [13][14][15][16][17][18][19]. A number of studies has shown a normalized breathing pattern and even improved exercise capacity in patients with CSA-CSR [16,19,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Control groups were sub therapeutic ASV (one study) , CPAP (two studies), BPV (one study) and optimal medical treatment (three studies). Five studies reported clear statements on AHI. Six studies involved outcomes of the LVEF.…”
Section: Resultsmentioning
confidence: 99%
“…deceleration time, ASV vs no treatment of sleep-disordered breathing: −43.9 ± 88.8 vs 12.4 ± 68.8, P > 0.05). 5 The proportion of patients whose diastolic dysfunction improved was non-significantly higher in the ASV than in the control group, respectively (37% vs 15%, P > 0.05). 5 These data provide estimates of effect size and justify the evaluation of the effects of positive airway pressure therapy on diastolic function in larger randomized controlled trials.…”
mentioning
confidence: 80%
“…5 The proportion of patients whose diastolic dysfunction improved was non-significantly higher in the ASV than in the control group, respectively (37% vs 15%, P > 0.05). 5 These data provide estimates of effect size and justify the evaluation of the effects of positive airway pressure therapy on diastolic function in larger randomized controlled trials. However, we did not assess the acute effects of positive airway pressure therapy on diastolic function, which might have complemented the presented data on blood pressure, heart rate and non-invasively assessed cardiac output.…”
mentioning
confidence: 80%